Light Quantum Induces The Measurement Paradox (JOURNAL OF ADVANCES IN PHYSICS, 2019)
We learn from Quantum Mechanics that the observation of the microscopic world, the measurement (M) of a quantum object, i.e. a particle, inexorably modifies the physical system we wish to examine.What happens is that with the M it takes place a reduction of the state vectors, that is the ‘wave function collapse’ of the measured particle.Why does it happen? No one knows.The enigma of the so-called Measurement Paradox, in our opinion, could be solved if we considered that the light quantum(LQ), as suggested by the Principle of Equivalence Mass-Energy, carries out a dynamic-mass equivalent to its energy. The LQ is indispensable to carry out a M. No M can be carried out without using the quantum of light.Calculus show that a photon of the optic band hits an electron with a momentum bigger than the mass of the electron itself.This may explain why the M induces the implosion of the quantum object observed, together with the collapse of its wave function, giving rise to the Measurement Paradox.